LyGo: A Platform for Rapid Screening of Lytic Polysaccharide Monooxygenase Production - Hernández-Rollán, Cristina; Falkenberg, Kristoffer B; Rennig, Maja; Bertelsen, Andreas B; Ipsen, Johan Ø; Brander, Søren; Daley, Daniel O; Johansen, Katja S; Nørholm, Morten H. H (ACS synthetic biology, 2021)
Environmentally friendly sources of energy and chemicals are essential constituents of a sustainable society. An important step toward this goal is the utilization of biomass to supply building blocks for future biorefineries. Lytic polysaccharide monooxygenases (LPMOs) are enzymes that play a critical role in breaking the chemical bonds in the most abundant polymers found in recalcitrant biomass, such as cellulose and chitin. To use them in industrial processes they need to be produced in high titers in cell factories. Predicting optimal strategies for producing LPMOs is often nontrivial, and methods allowing for screening several strategies simultaneously are therefore needed. Here, we present a standardized platform for cloning LPMOs. The platform allows users to combine gene fragments with 14 different expression vectors in a simple 15 min reaction, thus enabling rapid exploration of several gene contexts, hosts, and expression strategies in parallel. The open-source LyGo platform is accompanied by easy-to-follow online protocols for both cloning and expression. As a demonstration of its utility, we explore different strategies for expressing several different LPMOs in Escherichia coli, Bacillus subtilis, and Komagataella phaffii.